Análise da associação bactéria-macroalgas em ambiente marinho e do seu potencial uso na avaliação ambiental - Maurat, Maria Cristina da Silva (Universidade Federal de São Carlos, 2003)
In the last decades the increase in the amount of nutrients, particularly nitrogen and phosphorus, introduced into the sea, has brought an accelerated eutrophication of the coastal marine ecosystems, and great changes in water, sediment and biotic communities. Nutrient enrichment is usually associated to other pollutants, as the heavy metals. The use of macroalgae and heterotrophic bacteria has been considered an efficient tool in environmental diagnosis when focusing these two types of pollution. The aim of the present study was to compare the biomass of bacteria in the water column, attached to the macroalgae and in the sediment of Praia da Baleia (Angra dos Reis/RJ), a region used as control and of Praia de Boa Viagem (Niterói/RJ), a region where the main impact is from domestic sewage effluents evaluating the effect of the eutrophication associated to different concentrations of zinc on Champia parvula and accompanying microorganisms by using laboratory experimentation. Methods involved filtration of samples on nuclepore filters, detachment of bacteria by mechanical shaking and ultrasounding, then cell enumeration by epifluorescence and the use of conversion factors to calculate biomass as organic carbon. The highest bacteria biomass in the water, sediment and macroalgae was obtained for in Praia de Boa Viagem. The evaluation of bacteria biomass in different substrates has shown a direct correlation with the trophic state of the environment, with mean values of 0,198 µgC.cm-3 in the water; of 1,29 µgC.cm-3 in sediment and 0,038 µgC.cm-3 in the macroalgae at the area impacted, values higher than those found in the control area. Chronic and semi-estatic toxicity tests were also performed along 15 days in order to determine growth rates, mortality, and morphological changes in the fronds of the macroalgae Champia parvula, grown on different combinations of nutrients levels, zinc concentrations and presence or absence of bacteria. Laboratory experiments evidenced that zinc and nutrient concentrations interfere with growth, mortality and morphology of C. parvula and also that macronutrients and bacteria probably influenced the accumulation of zinc by the macroalgae, thus influencing its growth.
Keywords: Biologia marinha; Ecotoxicologia; Bioindicadores; Macroalgas; Poluição marinha; Associação bactéria-alga; Champia parvula; Ecotoxicology; Bioindicators; Bacteria-algae association; Macroalgae; Marine pollution; Champia parvula; CIENCIAS BIOLOGICAS::ECOLOGIA